Implementation of Islamic Educational Leadership in the Digital Era Among Gen Z - Mashuri Mashuri; Junaidi Junaidi; Aulia Ramadona; Lia Amelia; Yusnimar Yusri (International Journal of Educational Narratives, 2025)
Background. The digital era has brought about significant changes in communication, learning, and leadership patterns, including in the context of Islamic education. Purpose. This study aims to examine how to implement effective Islamic educational leadership in the digital era, especially in fostering and guiding students from Generation Z. Method. This research employed a qualitative approach with a literature review. Data were collected from various scientific journals, books, and relevant research reports on Islamic educational leadership, the characteristics of Gen Z, and the influence of digitalization in education. Results. The study results show that transformational and participatory leadership that utilizes digital platforms such as social media, e-learning, and online communication is very effective in reaching Gen Z. Conclusion. Implementing Islamic educational leadership in the digital era requires leaders who are adaptive, visionary, and capable of integrating Islamic values with digital technology.